Fever of unknown origin and pancytopenia caused by culture-proven delayed onset disseminated bacillus Calmette-Guérin (BCG) infection after intravesical instillation. (9th April 2013) - Dammert, Pedro; Boujaoude, Ziad; Rafferty, William; Kass, Jonathan
Abstract : A 78-year-old man was diagnosed with bladder carcinoma in situ and was successfully treated with intravesical bacillus Calmette-Guérin (BCG) instillations. At 6 months after the last dose, he developed fever, weight loss and malaise. He had an extensive negative workup at an outside hospital and was treated empirically with ciprofloxacin for 2 weeks. The fever resolved but returned months later and he was readmitted with pancytopenia, elevated alkaline phosphatase and ground glass opacities on the chest CT. Bone marrow and liver biopsies showed non-caseating granulomas and were negative for acid-fast bacillus (AFB) and fungal stains. Mycobacterium tuberculosis complex PCR of the bone marrow was negative. Owing to the high clinical suspicion of disseminated BCG infection, the patient was treated empirically. After 9 weeks of incubation, the bone marrow AFB culture grew Mycobacterium bovis . Within 2 months of treatment his symptoms resolved and his laboratory results normalised.